VIBRATIONS OF TWO-LAYERED PLATES IN CASE OF SLIDING CONTACT BETWEEN CONTACT SURFACES OF THE PLATE - Grishko, A.M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
The equations of oscillations of a two-layer plate are obtained on the basis of the assumption of Kirchhoff's hypothesis concerning the packet as a whole when the contact surfaces of the plate can slide freely relative to each other. It is assumed that the tangential stresses in the boundary conditions on the contact surface of the plates are zero. The dependence of bending and planar vibrations is obtained. The conditions for the appearance of a resonance are obtained.
Keywords: two-layered plates, Navier conditions, sliding contact, hinging edge.